2005
DOI: 10.1051/radiopro:2005s1-009
|View full text |Cite
|
Sign up to set email alerts
|

Capability of the Kd model to predict radionuclides behaviour and transport in unsaturated columns under steady flow conditions

Abstract: Abstract. In the frame of the IRSN Chernobyl Pilot Site Project, a waste trench containing hot particles was instrumented to study the fate of radioactive pollutants. Cs in the Aeolian sand in both saturated and unsaturated conditions. Batch experiments were performed to study the chemical equilibrium state of the soil/solution system under static conditions. Stirred flow-through reactor experiments were performed to study the kinetics and reversibility of sorption reactions at the surface of solid particles u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The flowand-transport model shows that this migration can be reproduced by considering reversible 90 Sr sorption processes within both waste material and underlying sand, e.g., through the linear equilibrium sorption concept, combined with a vertical percolation flow. The reversibility of the 90 Sr sorption in the Chernobyl eolian sandy deposit was already highlighted through laboratory experiments (Ardois and Szentnect, 2005). These experiments also showed that the 90 Sr sorption can be perfectly described by the same ion exchange model whatever the water content.…”
Section: Migration Of 90 Srmentioning
confidence: 75%
“…The flowand-transport model shows that this migration can be reproduced by considering reversible 90 Sr sorption processes within both waste material and underlying sand, e.g., through the linear equilibrium sorption concept, combined with a vertical percolation flow. The reversibility of the 90 Sr sorption in the Chernobyl eolian sandy deposit was already highlighted through laboratory experiments (Ardois and Szentnect, 2005). These experiments also showed that the 90 Sr sorption can be perfectly described by the same ion exchange model whatever the water content.…”
Section: Migration Of 90 Srmentioning
confidence: 75%
“…These empirical models mitigate the Kd hypothesis by assuming that sorption occurs on 2-3 different types of solid sites, governed by equilibrium and/or kinetic rates. In the laboratory, the EK approaches better describe non-equilibrium 137Cs sorption observed in batch sorption experiments (Lee et al, 2013;Valcke and Cremers, 1994), stirred flow-through reactors, and soil columns (Ardois and Szenknect, 2005;Szenknect et al, 2003). However, in field conditions, evidences that equilibrium-kinetic sorption explain observed 137Cs migration are still limited.…”
Section: Introductionmentioning
confidence: 99%